The structural stability, lattice dynamics, electronic, thermophysical, and mechanical properties of the inverse perovskites A3OX: A comparative first‐principles study. (11th November 2020) - Sattar, Muhammad A.; Javed, Mehreen; Benkraouda, Maamar; Amrane, Noureddine
Summary: We present a comparative study on the structural, electronic, elastic, and thermoelectric properties of the cubic inverse‐perovskites A3 OX (where A = Li, Na, K and X = Cl, Br, I) by density functional theory (DFT). The cohesive, formation, and elastic properties analysis indicates that all studied materials are chemically, thermodynamically, and mechanically stable. Electronic properties reveal that all the inverse A3 OX perovskite are direct bandgap semiconductors except Li3 OCl and Li3 OBr with ionic nature which is confirmed by electron localization function (ELF) analysis. We have also calculated Debye temperature ( Θ D ) and Grüneisen parameter (γ) to determine the lattice thermal conductivity for all the A3 OX materials. Furthermore, thermoelectric (TE) properties are explored by calculating the Seebeck coefficient ( S ), electronic thermal conductivity, power factor (PF), electrical conductivity ( σ / τ ), lattice thermal conductivity, and ZT value. Our investigated A3 OX inverse‐perovskites provide a fertile base that can improve the overall TE performance for TE applications and green energy production. Abstract : The studied inverse A3OX (A=Li, Na, K & X=Cl, Br, I) perovskites are chemically, thermodynamically, mechanically and vibrationally stable compounds. These A3OX antiperovskites are found to be direct bandgap semiconductors except Li3OCl and Li3OBr with energy bandgap ranging from 2 eV to 4.6 eV. At 1000K, the highest value of ZT is found 0.52 and 0.42 for the Na3OI and K3OCl antiperovskites.